Does the Interest Rate Form Business Cycle? - Bidabad, Bijan; Hassan, Abul (International Journal of Accounting & Finance Review, 2019)
Dynamic structural behavior of depositor, bank and borrower and the role of banks in forming business cycle are investigated. We test the hypothesis that does banks behavior make oscillations in the economy through the interest rate. By dichotomizing banking activities into two markets of deposit and loan, we show that these two markets have non-synchronized structures, and this is why the money sector fluctuation starts. As a result, the fluctuation is transmitted to the real economy through saving and investment functions. Empirical results assert that in the USA, the banking system creates fluctuations in the money sector and real economy as well through short-term interest rates